A randomized, double‐blind, crossover study of the effect of the fluoroquinolone moxifloxacin on glucose levels and insulin sensitivity in young men and women. Issue 1 (12th September 2022) - Juhl, Christian R.; Burgdorf, Josephine; Knudsen, Cecilie; Lubberding, Anniek F.; Veedfald, Simon; Isaksen, Jonas L.; Hartmann, Bolette; Frikke‐Schmidt, Ruth; Mandrup‐Poulsen, Thomas; Holst, Jens J.; Kanters, Jørgen K.; Torekov, Signe S.
Abstract: Aim: The voltage‐gated potassium channel Kv 11.1 is important for repolarizing the membrane potential in excitable cells such as myocytes, pancreatic α‐ and β‐cells. Moxifloxacin blocks the Kv 11.1 channel and increases the risk of hypoglycaemia in patients with diabetes. We investigated glucose regulation and secretion of glucoregulatory hormones in young people with and without moxifloxacin, a drug known to block the Kv 11.1 channel. Materials and Methods: The effect of moxifloxacin (800 mg/day for 4 days) or placebo on glucose regulation was assessed in a randomized, double‐blind, crossover study of young men and women (age 20‐40 years and body mass index 18.5‐27.5 kg/m 2 ) without chronic disease, using 6‐h oral glucose tolerance tests and continuous glucose monitoring. Results: Thirty‐eight participants completed the study. Moxifloxacin prolonged the QTcF interval and increased heart rate. Hypoglycaemia was more frequently observed with moxifloxacin, both during the 8 days of continuous glucose monitoring and during the oral glucose tolerance tests. Hypoglycaemia questionnaire scores were higher after intake of moxifloxacin. Moxifloxacin reduced the early plasma‐glucose response (AUC0‐30 min ) by 7% (95% CI: −9% to −4%, p  < .01), and overall insulin response (AUC0‐360 min ) decreased by 18% (95% CI: −24% to −11%, p  < .01) and plasma glucagon increased by 17% (95% CI: 4%‐33%, p  = .03). Insulin sensitivity calculated as the Matsuda index increased by 11%, and MISI, an index of muscle insulin sensitivity, increased by 34%. Conclusions: In young men and women, moxifloxacin, a drug known to block the Kv 11.1 channel, increased QT interval, decreased glucose levels and was associated with increased muscle insulin sensitivity and more frequent episodes of hypoglycaemia.